Assessment of the normal anal position index (API) of Indonesian neonates - Yudi Suryana; Akhmad Makhmudi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
The existing anal position index (API) data appear to vary among the ethnic differences.Until now, however, the normal API has not been studied in Indonesia. This study aimedto determine the normal value of the API in Indonesian newborns This cross-sectionalstudy was conducted on 62 neonates (29 males and 33 females) without any malformationat Pediatric Surgery Division, Department of Surgery, Dr. Sardjito General Hospital,Yogyakarta during the period September to October 2012. The position of the anus wasnumerically defined by the API, which is the ratio of anus-fourchette distance in females and anus-scrotum distance in males to the distance between coccyx and fourchette/scrotum. To make correct measurements, transparent adhesive tape was used longitudinally on midperinum in a way that it covered the anus. Then fourchette/scrotum, anus center and the lower margin of coccyx were marked on it. Distances marked on each tape were then measured with the standard ruler. Relationship between API and other parameters were analyzed. The API values were 0.46±0.05 (95% CI: 0.44–0.48) for newborn males and 0.37±0.07 (95% CI: 0.35–0.39) for newborn females. The difference of API between males and females was significant (p = 0.000). API had no significant correlation with gestational age (p = 0.350) and birth weight (p = 0.650). Our data suggested the API, which is sex dependent, provides a reliable parameter for determining the position of the anus. API has no correlation with gestational age and birth weight. The determination of normal API in older infants is required to determine whether the API is affected by age.